Cooling dynamics of self‐assembled monolayer coating for integrated gold nanocrystals on a glass substrate. (1st January 2015) - Ichiyanagi, Kouhei; Sekiguchi, Hiroshi; Sato, Tokushi; Nozawa, Shunsuke; Tomita, Ayana; Hoshino, Manabu; Adachi, Shin‐ichi; Sasaki, Yuji C.
<x xml:space="preserve">Abstract</x> Picosecond time‐resolved X‐ray diffraction has been used to study the nanoscale thermal transportation dynamics of bare gold nanocrystals and thiol‐based self‐assembled monolayer (SAM)‐coated integrated gold nanocrystals on a SiO2 glass substrate. A temporal lattice expansion of 0.30–0.33% was observed in the bare and SAM‐coated nanocrystals on the glass substrate; the thermal energy inside the gold nanocrystals was transported to the contacted substrate through the gold–SiO2 interface. The interfacial thermal conductivity between the single‐layered gold nanocrystal film and the SiO2 substrate is estimated to be 45 MW m−2 K−1 from the decay of the Au 111 peak shift, which was linearly dependent on the transient temperature. For the SAM‐coated gold nanocrystals, the thermal dissipation was faster than that of the bare gold nanocrystal film. The thermal flow from the nanocrystals to the SAM‐coated molecules promotes heat dissipation from the laser‐heated SAM‐coated gold nanocrystals. The thermal transportation of the laser‐heated SAM‐coated gold nanocrystal film was analyzed using the bidirectional thermal dissipation model.